Assigning a different endoscopist for each annual follow-up may contribute to improved gastric cancer detection rates - Unno, Shuhei; Igarashi, Kimihiro; Saito, Hiroaki; Hirasawa, Dai; Okuzono, Toru; Tanaka, Yukari; Nakahori, Masato; Matsuda, Tomoki (Endoscopy International Open, 2022)
Background and study aims Esophagogastroduodenoscopy (EGD) is an effective and important diagnostic tool to detect gastric cancer (GC). Although previous studies show that examiner, patient, and instrumental factors influence the detection of GC, we analyzed whether assigning a different examiner to surveillance EGD would improve the detection of GC compared to assigning the same examiner as in the previous endoscopy.Patients and methods We retrospectively reviewed patients who underwent two or more consecutive surveillance EGDs at a single center between 2017 and 2019. We identified factors associated with GC detection using multivariable regression analysis and propensity-score matching.Results Among 7794 patients, 99 GC lesions in 93 patients were detected by surveillance EGD (detection rate; 1.2 %), with a mean surveillance interval of 11.2 months. Among the detected 99 lesions, 87 (87.9 %) were curatively treated with endoscopy. There were no differences in the clinicopathologic characteristics of GC detected by the same or different endoscopists. GC detection in the group examined by different endoscopists was more statistically significant than in the group examined by the same endoscopist, even after propensity-score matching (1.6 % and 0.7 %; P < 0.05). Endoscopic experience and other factors were not statistically significant between the two groups.Conclusions In surveillance EGD, having a different endoscopist for each exam may improve GC detection rates, regardless of the endoscopist’s experience.